Opportunities of renewable energy use in Hajdú-Bihar and Szabolcs-Szatmár-Bereg counties - Tamás, András (Acta Agraria Debreceniensis, 2015)
Today it’s an important role of the renewable energy resources, improving energy efficiency, thereby contributing to sustainable, ecofriendly use of local energy resources. Globally intensify the requirements and considerations related to environmental conservation. In this light, the main objective of the Hungarian energy concept is to maintain long-term security of supply, the economy and the environment occurring contradictions. So there is a need for systems that, in compliance with EU environmental directives, acceptable cost level will ensure the desired and expected security of supply. In the study, three companies and other technical parameters of these are examined. For each undertaking, different results were observed. For two undertakings, we are talking about realized investments, in one case a prognosis was examined. All three companies contributed to the requirement of renewable energy sources reaching 13% in Hungary by 2020.